Pengaruh Komitmen Organisasi, Sistem Pengendalian Internal, Kompetensi Pemerintah Desa, Transparansi, dan Aksesibilitas Laporan Keuangan Terhadap Akuntabilitas Pengelolaan Dana Desa - Dewi Indriasih; Aminul Fajri; Dinda Febriana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This purpose of this study is to determine the effect of commitment of village government organization, internal control system, village government competence, transparency, and accessibility of financial reports on the management of village funds at the village government office in Petarukan District, Pemalang Regency. The population in this study is village government officials in Petarukan District, Pemalang Regency, which consists of 19 villages. The sampling technique was a saturated sample consisting of the village head, village secretary, village treasurer, and BPD with a total of 76 respondents. This research was conducted using descriptive quantitative methods. The data analysis method used is multiple linear regression analysis using the SPSS program. The results of this study are: 1. The commitment of village government organization affects the Accountability of Village Fund Management. 2. The Internal Control System affects the Accountability of Village Fund Management. 3. The competence of the Village Government affects the Accountability of Village Fund Management. 4. Transparency affects Village Fund Management Accountability. 5. Accessibility of Financial Statements affects Village Fund Management Accountability